2001
DOI: 10.1046/j.1532-5415.2001.4911243.x
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Age and Cervical Cancer Screening and Prognosis

Abstract: The disproportionate burden of cervical cancer observed in older women appears to be largely attributable to lack of screening within the 3 years before diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 26 publications
2
26
0
2
Order By: Relevance
“…The odds of CC screening service uptake among women in the age range of 30-39 years were 2.78 times higher than women aged 21-29 years old. Similar findings were also reported both in developing and developed countries [25,26]. This is not surprising as women at the age of 30s and 60s are more likely to be symptomatic due to the bimodal distribution nature of the CC, which may enhance their probability of screening for CC.…”
Section: Discussionsupporting
confidence: 72%
“…The odds of CC screening service uptake among women in the age range of 30-39 years were 2.78 times higher than women aged 21-29 years old. Similar findings were also reported both in developing and developed countries [25,26]. This is not surprising as women at the age of 30s and 60s are more likely to be symptomatic due to the bimodal distribution nature of the CC, which may enhance their probability of screening for CC.…”
Section: Discussionsupporting
confidence: 72%
“…Once diagnosed, older women are more likely to die of cervical cancer within 3 years, mostly because of the extent of the disease at diagnosis [16]. In addition, older women are more likely to receive inferior treatment for their disease.…”
Section: Discussionmentioning
confidence: 99%
“…A study done in Florida also revealed that elderly women were more likely to be diagnosed at an advanced stage and each additional year of age was associated with 3% increased odds of advanced cervical cancer diagnosis [55]. Previous researches in the USA have documented that older women are significantly less likely than younger women to undergo Pap testing [62][63][64] and therefore are more likely to present with advanced stage. In low middle-income countries, older women were also found to have long help-seeking intervals for their symptoms and were more likely to be diagnosed with advanced stage cervical cancer [50,52,56,65].…”
Section: Discussionmentioning
confidence: 99%